PENGARUH PEMBERIAN PAKAN KEONG MAS TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP LOBSTER PASIR (Panulirus homarus) - Witari Anggraini; Zaenal Abidin; Saptono Waspodo (Universitas Mataram, 2018)
The aim of study was to determine the effect of feeding apple snails on the growth and survival of sand lobster (panulirus homarus). The experiment used Completely Randomized Design with five different treatments. The treatments were P1 (100% trash fish as control), P2 (50% trash fish + 50% fresh apple snail), P3 (50% trash fish + 50% processed apple snail), P4 (100% fresh apple snail), and P5 (100% processed apple snail). The data obtained were analyzed using analysis of variance (ANOVA) with a significant level of 5% and Duncan test was carried out with a significant level of 5% to find out the best treatment. Based on the results of the study showed that all treatments had a significantly different effect (p<0.05) on absolute growth, specific growth, feed conversion ratio and feed efficiency. Feeding 100% fresh apple snail is the best treatment compared to other treatments.